Appraisal of Post-Harvest Drying and Storage Operations in Africa: Perspectives on Enhancing Grain Quality - Baidhe, Emmanuel; Clementson, Clairmont L; Senyah, Judith; Hammed, Ademola (MDPI AG, 2024)
Grain quality is largely driven by grain infrastructure (technology) and handling practices (application of knowledge on handling). The use of inappropriate infrastructure and inappropriate handling protocols poses food safety and health-related risks. This review provides evidence for the link between drying and storage operations in the context of preserving grain quality. The purpose of this study was to evaluate the close grain quality relationship between drying and storage, with an appraisal of operations in Africa. This study further benchmarked successful and scalable models in Africa to infer guidance for promotion of optimal and effective drying and storage initiatives. While open-sun drying is undoubtedly the most adopted approach to grain drying for the rural-poor farmers, this study revealed greater success in grain storage, especially with the breakthrough at the introduction and adoption of small-scale hermetic storage technologies. Upon assessment of the cob, WFP Zero Food Loss Initiative, and AflaSight models implemented in Rwanda and Uganda, this study suggests: (i) the adoption of system thinking; (ii) the use of sustainable approaches such as gender inclusion, sustainable financing options, and use of existing infrastructures along-side novel interventions; and (iii) enabling policies and political will as strategic pathways for successful implementation of improved grain-quality interventions during drying and storage. In the short term, grain handlers must develop appropriate grain management protocols during open-sun drying to limit the impact of drying-related grain quality deterioration. Consortia-based implementation of the three models evaluated in this review could improve grain quality, food security and safety, and market linkages with premium grain markets, fostering economic growth and transformation. Agricultural Science Database